Neonatal encephalopathy: Etiologies other than hypoxic-ischemic encephalopathy. Issue 5 (October 2021) - Sandoval Karamian, A.G.; Mercimek-Andrews, S.; Mohammad, K.; Molloy, E.J.; Chang, T.; Chau, Vann; Murray, D.M.; Wusthoff, Courtney J.; ,
Abstract: Neonatal encephalopathy (NE) describes the clinical syndrome of a newborn with abnormal brain function that may result from a variety of etiologies. HIE should be distinguished from neonatal encephalopathy due to other causes using data gathered from the history, physical and neurological exam, and further investigations. Identifying the underlying cause of encephalopathy has important treatment implications. This review outlines conditions that cause NE and may be mistaken for HIE, along with their distinguishing clinical features, pathophysiology, investigations, and treatments. NE due to brain malformations, vascular causes, neuromuscular causes, genetic conditions, neurogenetic disorders and inborn errors of metabolism, central nervous system (CNS) and systemic infections, and toxic/metabolic disturbances are discussed.